Organocatalytic Asymmetric One‐Step Desymmetrizing Dearomatization Reaction of Indoles: Development and Bioactivity Evaluation. (4th December 2018) - Peng, Lei; Xu, Da; Yang, Xiaohong; Tang, Jiakun; Feng, Xuli; Zhang, Shao‐Lin; Yan, Hailong
Abstract: An organocatalytic one‐step desymmetrizing dearomatization reaction of indoles with in situ formed vinylidene ortho ‐quinone methides is reported. A set of [6‐6‐5] and/or [5‐6‐5] fused indoline heterocycles were obtained in excellent yields with excellent diastereoselectivities (>20:1 d.r.) and enantioselectivities (up to 99 % ee ). Moreover, some of the obtained products were screened against a panel of cancer cell lines, and one was identified to inhibit the proliferation of all the tested cancer cells, but showed marginal effects against non‐cancerous cells. The methodology provides a platform for the synthesis of new leading compounds with antitumor activity.